Diversity and Functionality of Culturable Endophytic Bacterial Communities in Chickpea Plants - Brigido, Clarisse (2019)
The aims of this study were to isolate, identify and characterize culturable endophytic bacteria from chickpea (Cicer arietinum L.) roots grown in different soils. In addition, the effects of rhizobial inoculation, soil and stress on the functionality of those culturable endophytic bacterial communities were also investigated. Phylogenetic analysis based on partial 16S rRNA gene sequences revealed that the endophytic bacteria isolated in this work belong to the phyla Proteobacteria, Firmicutes and Actinobacteria, with Enterobacter and Pseudomonas being the most frequently observed genera. Production of indoleacetic acid and ammonia were the most widespread plant growth-promoting features, while antifungal activity was relatively rare among the isolates. Despite the fact that the majority of bacterial endophytes were salt- and Mn-tolerant, the isolates obtained from soil with Mn toxicity were generally more Mn-tolerant than those obtained from the same soil amended with dolomitic limestone. Several associations between an isolate’s genus and specific plant growth-promoting mechanisms were observed. The data suggest that soil strongly impacts the Mn tolerance of endophytic bacterial communities present in chickpea roots while rhizobial inoculation induces significant changes in terms of isolates’ plant growth-promoting abilities. In addition, this study also revealed chickpea-associated endophytic bacteria that could be exploited as sources with potential application in agriculture